The Economic Foundations of Firefighting Organizations and Institutions - Lueck, Dean; Yoder, Jonathan (Journal of forestry, 2015)
This article examines the complex structure of wildland firefighting using the economic theories of contracts, property rights, and organization. We examine historical and cross-sectional case studies and consider the implications for contemporary wildfire management. Wildfires have characteristics that make their management and control complex and seemingly inefficient. Their occurrence has great spatiotemporal variance, and preparation and timeliness are crucial for effective suppression. Fires tend not to coincide with landownership boundaries, which affect private and public incentives to fight fires. Firefighting institutions vary substantially over time and space, ranging from private individual and cooperative action to large-scale centralized government intervention, military style organization, specialization, and prepositioned investments. We examine the implications of how incentives can affect suppression and asset protection decisions in the face of changing land use and land cover and how these changes can affect firefighting costs and other outcomes such as fire size.